Effective signage design for shopping mall, Malaysia / Nurul Amiera Sofea Mazlan - Mazlan, Nurul Amiera Sofea (2021)
This study investigates how signages characteristic selection can affect visitor and end user to find their wayfinding in public space especially in shopping mall environment. The current issues that relate to signages system in shopping mall is the suitability of signage types and design that may contribute to confusing, people may lost or overlooked due to the size or befitting in public space. The objective for this research is to identify main issues relate to signages system in shopping mall, determine design characteristic and criteria and to proposed new signages design criteria that more efficient. Methods for this research is qualitative that narrow to structured literature review analysis. Outcomes for this research is absolutely to introduce combination signages between physical signages with digital signages that more efficient for wayfinding in shopping mall.